2012
DOI: 10.1088/0169-5983/44/5/055504
|View full text |Cite
|
Sign up to set email alerts
|

Free convection in parallelogram-shaped enclosures with isothermal active walls: viscous shear stress in active systems

Abstract: Thermocouples are often used for thermoregulation of active thermal systems. When the junctions of these sensors are under a natural convection flow, it is necessary to take into account the viscous stress that can affect the measurement of temperature and therefore the regulation set points. The main objective of this work is to study the viscous shear stress taking place close to the active hot wall in closed air-filled cavities of parallelogrammic shape. The influence of shear stress is examined for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The particular case of the parallelogram shaped cavity has some interesting applications in buildings and solar energy systems [1]. Natural convection studies [2][3][4] have been conducted in such geometries and have shown the influence of the angle between adjacent boundaries on the flow pattern and heat transfer.…”
Section: -Introductionmentioning
confidence: 99%
“…The particular case of the parallelogram shaped cavity has some interesting applications in buildings and solar energy systems [1]. Natural convection studies [2][3][4] have been conducted in such geometries and have shown the influence of the angle between adjacent boundaries on the flow pattern and heat transfer.…”
Section: -Introductionmentioning
confidence: 99%